Lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material and preparation method and application thereof
Through the preparation of lithium manganate/nitrogen doped graphene aerogel three-dimensional composite material, the problem of lithium manganate capacity decay during high-temperature cycle and high current charging and discharge is solved, the conductivity and cycle stability are improved, and the battery is reduced Self-discharge rate.
Patent Information
- Application Number
- CN202411374007.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-31
AI Technical Summary
As the cathode material of lithium ion batteries, lithium manganese oxide easily attenuates the capacity during high temperature cycle and high current charging and discharging. The main reasons are the low purity of the product, the Mn3+ surface distortion reaction, the low conductivity of lithium manganese oxide and the difficulty in deintercalation of lithium ion.
The preparation method of lithium manganese oxide/nitrogen doped graphene aerogel three-dimensional composite positive electrode material is adopted. By preparing lithium manganese oxide nanosheet materials and surface modification in the liquid phase process, combined with graphene oxide coating and sintering treatment, A lithium manganate/nitrogen doped graphene aerogel material formed with high conductivity and stable structure.
The conductive performance of lithium manganate is improved, the contact opportunity with the electrolyte is reduced, the reversible capacity and cycling performance is significantly improved, the self-discharge rate of the battery is reduced, and the cycling stability of the battery is improved.
Smart Images

Figure CN119230783A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery electrode materials, and in particular relates to a lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material and a preparation method and application thereof. Background Art
[0002] LMO (LiMn2O4) has been rapidly promoted in the market due to its high specific energy, non-toxicity, environmental friendliness, and stable charge and discharge current. Its main application electronic products include portable mobile devices, communications, electric vehicles, aerospace, power grid load regulation, etc. Although LMO is an ideal positive electrode material for lithium-ion batteries, its capacity is prone to decay during high-temperature cycles and high-current charge and discharge. The main reasons are: 1. In the preparation process, due to the failure to completely mix the raw materials, Mn3O4 impurities are easily generated locally in the product, resulting in low product purity; 2. In the late stage of discharge, at high concentrations of Mn 3+ The surface of the 2+ Dissolved in the electrolyte, resulting in the reversible reaction cannot proceed normally; 3. The occurrence of Taylor effect in the late discharge period leads to the destruction of the spinel structure of lithium manganese oxide; 4. The conductivity of lithium manganese oxide is low, and the lithium ion deintercalation process is difficult.
[0003] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material and its preparation method and application, aiming to solve the problem that the capacity of lithium manganese oxide material, as a positive electrode material for lithium-ion batteries, is easily attenuated during high-temperature cycling and high-current charging and discharging.
[0005] The technical solution of the present invention is as follows:
[0006] A method for preparing a lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material, comprising the steps of:
[0007] Preparation of lithium manganese oxide nanosheet materials;
[0008] In the liquid phase process, aminopropyltrimethoxysilane was used to modify the surface of lithium manganate nanosheets to obtain APS-LMO materials with positive surface charge.
[0009] The graphene oxide aqueous solution is slowly added dropwise to the APS-LMO material under continuous stirring. After sufficient stirring, the positively charged APS-LMO material is adsorbed on the negatively charged graphene oxide surface. After centrifugal drying, graphene oxide-coated lithium manganate is obtained, which is recorded as lithium manganate / graphene oxide.
[0010] The prepared lithium manganate / graphene oxide is dispersed in a urea solution, and then a graphene oxide dispersion is added thereto, and the uniformly mixed dispersion is poured into a reactor for heating treatment to obtain a reaction product;
[0011] The reaction product is freeze-dried and then sintered to obtain a lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material.
[0012] The method for preparing the lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material, wherein the step of preparing the lithium manganese oxide nanosheet material comprises:
[0013] dispersing the prepared graphite oxide in ethylene glycol to obtain a graphene oxide dispersion;
[0014] mixing ascorbic acid, lithium hydroxide and potassium permanganate to obtain a mixed solution;
[0015] The mixed solution was added into the graphene oxide dispersion and stirred, and Li + and Mn 3+ The mixture is adsorbed on the negatively charged graphene oxide surface, and the final mixture is poured into a reactor. After solvent thermal treatment, the product is filtered and washed out, and placed in a vacuum drying oven to dry, thereby obtaining a lithium manganate nanosheet material.
[0016] The method for preparing the lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material comprises the following steps: the temperature of the solvent thermal treatment is 160-180° C., and the time is 8-10 hours.
[0017] The method for preparing the lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material comprises the following steps: pouring the uniformly mixed dispersion into a reaction kettle for heating treatment, wherein the heating treatment temperature is 100-150° C. and the time is 2-4 hours.
[0018] The preparation method of the lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material, wherein in the step of freeze-drying the reaction product and then sintering it, the sintering is carried out in a 5 vol.% H2 / Ar mixed atmosphere, the sintering temperature is 550-650°C, and the time is 1-3h.
[0019] A lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material is prepared by any preparation method of the lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material described in the present invention.
[0020] An application of a lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material, wherein the lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material of the present invention is used to prepare a lithium battery positive electrode sheet.
[0021] Beneficial effects: The lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material prepared by the present invention improves the conductivity of lithium manganese oxide, reduces the chance of contact between lithium manganese oxide and electrolyte, and significantly improves the reversible capacity and cycle performance; on the other hand, the charge transfer impedance value of the synthetic material is reduced, the coulomb efficiency of the assembled experimental battery is increased, and the self-discharge rate of the battery is reduced. The lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material prepared by the present invention is used as a lithium battery positive electrode sheet. The assembled battery has been tested for charge and discharge rates. The charge and discharge specific capacities of 0.1C, 0.2C, 0.5C, and 1C are 155mAh / g, 150mAh / g, 80mAh / g, and 60mAh / g, respectively; the charge and discharge cycle at 1C rate is stable, indicating that the battery has good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A flow chart of a method for preparing a lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material of the present invention is shown;
[0023] Figure 2 This is the rate diagram of the lithium battery in Example 3.
[0024] Figure 3 This is the cycle characteristic diagram of the lithium battery in Example 3. DETAILED DESCRIPTION
[0025] The present invention provides a lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material and a preparation method and application thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0026] See also Figure 1 , Figure 1 The present invention provides a flow chart of a method for preparing a lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material, as shown in the figure, which comprises the steps of:
[0027] S10, preparing lithium manganese oxide nanosheet material;
[0028] Specifically, the prepared graphite oxide is dispersed in ethylene glycol to obtain a graphene oxide dispersion; ascorbic acid is mixed with lithium hydroxide and potassium permanganate to obtain a mixed solution; the mixed solution is added to the graphene oxide dispersion, and after stirring, Li is adsorbed by electrostatic adsorption. + and Mn 3+Adsorbed on the negatively charged graphene oxide surface, the resulting mixed solution is poured into a reactor, the product is filtered out after solvent thermal treatment, and placed in a vacuum drying oven for drying to obtain lithium manganate nanosheet material. In this embodiment, the solvent thermal treatment temperature is 160-180° C. and the time is 8-10 hours, but is not limited thereto.
[0029] S20, using aminopropyltrimethoxysilane to modify the surface of lithium manganate nanosheet material in a liquid phase process to obtain an APS-LMO material with a positively charged surface;
[0030] S30, slowly dropping the graphene oxide aqueous solution into the APS-LMO material under continuous stirring, and after sufficient stirring, the positively charged APS-LMO material is adsorbed on the negatively charged graphene oxide surface, and after centrifugal drying, graphene oxide-coated lithium manganate is obtained, which is recorded as lithium manganate / graphene oxide;
[0031] S40, dispersing the prepared lithium manganate / graphene oxide in a urea solution, then adding a graphene oxide dispersion thereto, pouring the uniformly mixed dispersion into a reactor for heating treatment to obtain a reaction product;
[0032] In this embodiment, the temperature of the heating treatment is 100-150° C. and the time is 2-4 hours, but it is not limited thereto.
[0033] S50, freeze-drying the reaction product and then sintering it to obtain a lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material.
[0034] In this embodiment, the sintering process is carried out in a 5 vol. % H2 / Ar mixed atmosphere, the sintering process temperature is 550-650°C, and the time is 1-3 hours, but it is not limited thereto.
[0035] The lithium manganese oxide / nitrogen doped graphene aerogel three-dimensional composite positive electrode material prepared by the present invention uses nitrogen doped graphene aerogel as a conductive skeleton, which, on the one hand, improves the conductivity of lithium manganese oxide, reduces the chance of lithium manganese oxide contacting with the electrolyte, and significantly improves the reversible capacity and cycle performance; on the other hand, the charge transfer impedance value of the synthetic material is reduced, the coulomb efficiency of the assembled experimental battery is increased, and the self-discharge rate of the battery is reduced. The lithium manganese oxide / nitrogen doped graphene aerogel three-dimensional composite positive electrode material prepared by the present invention is used as a positive electrode sheet of a lithium battery. The assembled battery has been tested for charge and discharge rates, and the charge and discharge specific capacities of 0.1C, 0.2C, 0.5C, and 1C are 155mAh / g, 150mAh / g, 80mAh / g, and 60mAh / g, respectively; the charge and discharge cycle at the 1C rate is stable, indicating that the battery has good cycle stability.
[0036] In some embodiments, a lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material is also provided, which is prepared by the preparation method of the lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material of the present invention.
[0037] In some embodiments, an application of a lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material is also provided, and the lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material described in the present invention is used to prepare a lithium battery positive electrode sheet.
[0038] The present invention will be further explained below by means of specific embodiments:
[0039] Example 1
[0040] Preparation of lithium manganese oxide nanosheets:
[0041] The prepared graphite oxide was dispersed in 40 mL of ethylene glycol (EG) to obtain a concentration of 4.0 mg mL -1 The graphene oxide dispersion was used as the solvent for the subsequent reaction. 0.1 g of ascorbic acid was added to a mixed solution of 40 mL of lithium hydroxide and potassium permanganate, wherein the concentration of lithium hydroxide was 0.1 mol / L and the concentration of potassium permanganate was 0.077 mol / L. The mixed solution was added to the graphene oxide dispersion and after sufficient stirring, Li was adsorbed by electrostatic adsorption. + and Mn 3+ The mixture was adsorbed on the negatively charged graphene oxide surface, and poured into a 50 mL reactor, and subjected to solvent thermal treatment at 170° C. for 9 h. The product was then filtered and washed, and placed in a vacuum drying oven to obtain a black lithium manganese oxide nanosheet material.
[0042] Preparation of lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite cathode material and battery assembly:
[0043] (1) Aminopropyltrimethoxysilane (APS) was used to modify the surface of lithium manganese oxide nanosheets (APS-LMO) in a liquid phase process to make their surface positively charged. Then, graphene oxide-coated lithium manganese oxide (lithium manganese oxide / graphene oxide) was prepared by electrostatic adsorption process, which is briefly described as follows: First, 20 mL of graphene oxide aqueous solution (0.75 mg mL -1 ) was slowly added dropwise to 200 mL of APS-LMO (0.4 mg mL -1 ) aqueous dispersion. After sufficient stirring, the positively charged APS-LMO will be adsorbed on the negatively charged graphene oxide surface, and lithium manganate / graphene oxide will be obtained after centrifugal drying. Then, the prepared lithium manganate / graphene oxide is dispersed in 13 mL (70 mg mL -1) urea solution, and then added 2 mL of graphene oxide solution (7.5 mg mL -1 ), after being mixed evenly, the above dispersion was poured into a 20 mL reactor and treated at 120°C for 3 h. Finally, it was freeze-dried and sintered at high temperature (sintered at 600°C for 2 h in a 5 vol.% H2 / Ar mixed atmosphere).
[0044] (2) Weigh 10% of the binder by mass and dissolve it in an appropriate amount of NMP. Centrifuge and stir for 1 hour to completely dissolve it, then add the conductive agent (conductive carbon black).
[0045] (3) The substances obtained in (1) and (2) are mixed completely and made into a uniform slurry, which is then coated on a metal aluminum foil, dried, pressed, and cut into a positive electrode sheet. A metal lithium sheet is used as the negative electrode, and 1 mol / L LiPF6 ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio of 1:1) is used as the electrolyte to assemble an experimental battery in a hand box filled with argon atmosphere.
[0046] Example 2
[0047] Preparation of lithium manganese oxide nanosheets:
[0048] The prepared graphite oxide was dispersed in 50 mL of ethylene glycol (EG) to obtain a concentration of 5.0 mg mL -1 The graphene oxide dispersion was used as the solvent for the subsequent reaction. 0.1 g of ascorbic acid was added to a mixed solution of 45 mL of lithium hydroxide and potassium permanganate, wherein the concentration of lithium hydroxide was 0.15 mol / L and the concentration of potassium permanganate was 0.087 mol / L. The mixed solution was added to the graphene oxide dispersion and after sufficient stirring, Li was adsorbed by electrostatic adsorption. + and Mn 3+ The mixture was adsorbed on the negatively charged graphene oxide surface, and poured into a 50 mL reactor, and subjected to solvent thermal treatment at 180° C. for 8 h. The product was then filtered out and washed, and placed in a vacuum drying oven to dry, thereby obtaining a black lithium manganese oxide nanosheet material.
[0049] Preparation of lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite cathode material and battery assembly:
[0050] (1) Aminopropyltrimethoxysilane (APS) was used to modify the surface of lithium manganese oxide nanosheets (APS-LMO) in a liquid phase process to make their surface positively charged. Then, graphene oxide-coated lithium manganese oxide (lithium manganese oxide / graphene oxide) was prepared by electrostatic adsorption process, which is briefly described as follows: First, 30 mL of graphene oxide aqueous solution (0.70 mg mL -1) was slowly added dropwise to 200 mL of APS-LMO (0.6 mg mL -1 ) aqueous dispersion. After sufficient stirring, the positively charged APS-LMO will be adsorbed on the negatively charged graphene oxide surface, and lithium manganate / graphene oxide will be obtained after centrifugal drying. Then, the prepared lithium manganate / graphene oxide is dispersed in 18 mL (70 mg mL -1 ) urea solution, and then 3 mL of graphene oxide solution (7.0 mg mL -1 ), after being mixed evenly, the above dispersion was poured into a 20 mL reactor and treated at 150°C for 3 h. Finally, it was freeze-dried and sintered at high temperature (sintered at 500°C for 2 h in a 5 vol.% H2 / Ar mixed atmosphere).
[0051] (2) Weigh 10% of the binder by mass and dissolve it in an appropriate amount of NMP. Centrifuge and stir for 1 hour to completely dissolve it, then add the conductive agent (conductive carbon black).
[0052] (3) The substances obtained in (1) and (2) are mixed completely and made into a uniform slurry, which is then coated on a metal aluminum foil, dried, pressed, and cut into a positive electrode sheet. A metal lithium sheet is used as the negative electrode, and 1 mol / L LiPF6 ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio of 1:1) is used as the electrolyte to assemble an experimental battery in a hand box filled with argon atmosphere.
[0053] Example 3
[0054] Preparation of lithium manganese oxide nanosheets:
[0055] The prepared graphite oxide was dispersed in 45 mL of ethylene glycol (EG) to obtain a concentration of 6.0 mg mL -1 The graphene oxide dispersion was used as the solvent for the subsequent reaction. 0.1 g of ascorbic acid was added to a mixed solution of 70 mL of lithium hydroxide and potassium permanganate, wherein the concentration of lithium hydroxide was 0.1 mol / L and the concentration of potassium permanganate was 0.087 mol / L. The mixed solution was added to the graphene oxide dispersion and after sufficient stirring, Li was adsorbed by electrostatic adsorption. + and Mn 3+ The mixture was adsorbed on the negatively charged graphene oxide surface, and poured into a 50 mL reactor, and subjected to solvent thermal treatment at 120° C. for 8 h. The product was then filtered out and washed, and placed in a vacuum drying oven to dry, thereby obtaining a black lithium manganese oxide nanosheet material.
[0056] Preparation of lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite cathode material and battery assembly:
[0057] (1) Aminopropyltrimethoxysilane (APS) was used to modify the surface of lithium manganese oxide nanosheets (APS-LMO) in the liquid phase process to make the surface positively charged. Then, the graphene oxide-coated lithium manganese oxide (lithium manganese oxide / graphene oxide) was prepared by electrostatic adsorption process, which is briefly described as follows: First, 20 mL of graphene oxide aqueous solution (0.70 mg mL -1 ) was slowly added dropwise to 250 mL of APS-LMO (0.4 mg mL -1 ) aqueous dispersion. After sufficient stirring, the positively charged APS-LMO will be adsorbed on the negatively charged graphene oxide surface, and lithium manganate / graphene oxide will be obtained after centrifugal drying. Then, the prepared lithium manganate / graphene oxide is dispersed in 15 mL (80 mg mL -1 ) urea solution, and then added 2 mL of graphene oxide solution (5.5 mg mL -1 ), after mixing evenly, the above dispersion was poured into a 20 mL reactor and treated at 220°C for 4 h. Finally, it was freeze-dried and sintered at high temperature (sintered at 650°C for 3 h in a 5 vol.% H2 / Ar mixed atmosphere).
[0058] (2) Weigh 10% of the binder by mass and dissolve it in an appropriate amount of NMP. Centrifuge and stir for 1 hour to completely dissolve it, then add the conductive agent (conductive carbon black).
[0059] (3) The substances obtained in (1) and (2) are mixed completely and made into a uniform slurry, which is then coated on a metal aluminum foil, dried, pressed, and cut into a positive electrode sheet. A metal lithium sheet is used as the negative electrode, and 1 mol / L LiPF6 ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio of 1:1) is used as the electrolyte to assemble an experimental battery in a hand box filled with argon atmosphere.
[0060] The battery assembled in Example 3 was tested for cycle performance, and the results are as follows: Figure 2 and Figure 3 As shown, the assembled battery of this embodiment has undergone a charge and discharge rate test, and the assembled battery has undergone a charge and discharge rate test, and the charge and discharge specific capacities of 0.1C, 0.2C, 0.5C, and 1C are 155mAh / g, 150mAh / g, 80mAh / g, and 60mAh / g, respectively; and the 1C rate charge and discharge cycle is stable, indicating that the battery has good cycle stability.
[0061] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material, characterized in that: Includes steps: Preparation of lithium manganese oxide nanosheet materials; In the liquid phase process, aminopropyltrimethoxysilane was used to modify the surface of lithium manganate nanosheets to obtain APS-LMO materials with positive surface charge. The graphene oxide aqueous solution is slowly added dropwise to the APS-LMO material under continuous stirring. After sufficient stirring, the positively charged APS-LMO material is adsorbed on the negatively charged graphene oxide surface. After centrifugal drying, graphene oxide-coated lithium manganate is obtained, which is recorded as lithium manganate / graphene oxide. The prepared lithium manganate / graphene oxide is dispersed in a urea solution, and then a graphene oxide dispersion is added thereto, and the uniformly mixed dispersion is poured into a reactor for heating treatment to obtain a reaction product; The reaction product is freeze-dried and then sintered to obtain a lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material.
2. The method for preparing the lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material according to claim 1, characterized in that: The steps of preparing lithium manganese oxide nanosheet material include: dispersing the prepared graphite oxide in ethylene glycol to obtain a graphene oxide dispersion; mixing ascorbic acid, lithium hydroxide and potassium permanganate to obtain a mixed solution; The mixed solution was added into the graphene oxide dispersion and stirred, and Li + and Mn 3+ The mixture is adsorbed on the negatively charged graphene oxide surface, and the final mixture is poured into a reactor. After solvent thermal treatment, the product is filtered and washed out, and placed in a vacuum drying oven to dry, thereby obtaining a lithium manganate nanosheet material.
3. The method for preparing the lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material according to claim 2, characterized in that: The temperature of the solvent thermal treatment is 160-180° C. and the time is 8-10 hours.
4. The method for preparing the lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material according to claim 1, characterized in that: The uniformly mixed dispersion is poured into a reaction kettle for heating treatment at a temperature of 100-150° C. for 2-4 hours.
5. The method for preparing the lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material according to claim 1, characterized in that: In the step of freeze-drying the reaction product and then sintering it, the sintering is carried out in a 5 vol.% H2 / Ar mixed atmosphere, the sintering temperature is 550-650°C, and the sintering time is 1-3 hours.
6. A lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material, characterized in that: The material is prepared by the method for preparing the lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material according to any one of claims 1 to 5.
7. An application of a lithium manganese oxide / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material, characterized in that: The lithium manganate / nitrogen-doped graphene aerogel three-dimensional composite positive electrode material described in claim 6 is used to prepare a positive electrode sheet for a lithium battery.
